Impaired oxygen extraction in metabolic myopathies: Detection and quantification by near-infrared spectroscopy - Grassi, Bruno; Marzorati, Mauro; Lanfranconi, Francesca; Ferri, Alessandra; Longaretti, Miriam; Stucchi, Andrea; Vago, Paola; Marconi, Claudio; Morandi, Lucia (Muscle & nerve, 2007)
Patients with mitochondrial myopathies (MM) or myophosphorylase deficiency (McArdle's disease, McA) show impaired capacity for O2 extraction, low maximal aerobic power, and reduced exercise tolerance. Non‐invasive tools are needed to quantify the metabolic impairment. Six patients with MM, 6 with McA, 25 with symptoms of metabolic myopathy but negative biopsy (patient‐controls, P‐CTRL) and 20 controls (CTRL) underwent an incremental cycloergometric test. Pulmonary O2 uptake (V̇O2) and vastus lateralis oxygenation indices (by near‐infrared spectroscopy, NIRS) were determined. Concentration changes of deoxygenated hemoglobin and myoglobin (Δ[deoxy(Hb + Mb)]) were considered an index of O2 extraction. Δ[deoxy(Hb + Mb)] peak (percent limb ischemia) was lower in MM (25.3 ± 12.0%) and McA (18.7 ± 7.3) than in P‐CTRL (62.4 ± 3.9) and CTRL (71.3 ± 3.9) subjects. V̇O2 peak and Δ[deoxy(Hb + Mb)] peak were linearly related (r2 = 0.83). In these patients, NIRS is a tool to detect and quantify non‐invasively the metabolic impairment, which may be useful in the follow‐up of patients and in the assessment of therapies and interventions. Muscle Nerve, 2006